A novel multilayer sandwich fabric-based composite material for infrared stealth and super thermal insulation protection. (15th March 2019) - Xu, Rui; Wang, Wei; Yu, Dan
Abstract: At present, infrared stealth materials for advanced detection and stealth technology is usually prepared with low emissivity coating on the surface, but there are very few efficient infrared stealth materials based on textiles with lightweight and flexible features. In this paper, we designed a carbon nanotube-doped aerogel (CNTAs) sandwich structure on polyimide (PI) fabric by hot pressing and then coated with a low emissivity Al-doped ZnO (ZAO) on the outer surface. The surface emissivity lower than 0.5 due to the existence of ZAO and the thermal conductivity of the intermediate interlayer aerogels as low as 0.013 W/(m·K). Additionally, through experiments, theoretical derivation and simulation analysis, we found the resultant composite demonstrated a high infrared stealth performance with super insulation effect, implying it will have a fine prospect in infrared stealth and thermal insulation protection fields with its unique structure and excellent properties.